Maternal and newborn health prioritization in Yobe State, Nigeria: analysis of stakeholders’ perspective - Emilia Ngozi Iwu; Charity Pring’ar Maina; Rifkatu Sunday Aimu; Rejoice Helma Abimiku; Sussan Israel-Isah; Kazeem Olalekan Ayodeji; George Odonye; Hadiza Sabo; Naoko Kozuki; Mamothena Mothupi (Conflict and Health)
Abstract Background Maternal and newborn mortality and morbidity in conflict-affected northeastern areas of Nigeria, such as Yobe State, are disproportionately higher than those in the rest of the country. There is limited evidence on the factors that influence maternal and newborn health (MNH) policymaking and implementation in this region, particularly with respect to the impact of conflict and context-specific issues. This study explores the political, economic and health system factors that drive the prioritization of MNH policies in Yobe State. The aim of this study was to elucidate the conflict-related factors influencing MNH outcomes, which could inform targeted interventions to improve MNH. Methods The study is a descriptive case study that relies on multiple data sources and is guided by the Health Policy Analysis Triangle. We reviewed national and subnational research, technical reports and policies related to reproductive health and the MNH in Nigeria since 2010. Following stakeholder mapping, we identified and invited prospective participants in the MNH policymaking space. Nineteen stakeholders from the government, civil society and nongovernmental organizations, donor agencies, and public and private sector health providers in Yobe State participated in the semistructured in-depth interviews. Data were collected from November 2022 through January 2023 and were thematically analysed via Dedoose software. Findings MNH services in Yobe State have received considerable attention through initiatives such as the National Midwifery Service Scheme, free MNH services, training of midwives with deployment to rural areas, and health facility renovations. The effective implementation of MNH services and policies faces challenges due to insufficient funding, and sustainability is hampered by changes in governance and political transitions. The Boko Haram insurgency exacerbated the humanitarian crisis in Yobe State and disrupted MNH services due to the displacement of populations and the decline in the number of health workers. Additionally, sociocultural and religious beliefs hinder timely access to and utilization of MNH services. Although policies and guidelines for MNH services exist in the state, they are inadequately disseminated to health providers, which affects their effective implementation across facilities. Collaboration and intersectoral coordination platforms exist, but competition and rivalries among unions, political entities, and implementing agencies sometimes impede progress. Conclusion Enhancing MNH services in Yobe state requires increased commitment for funding through the Northeast Development Commission rehabilitation fund; strengthening the health workforce, safety and retention plan; promoting gender inclusivity within the health sector; and addressing sociocultural barriers to women’s health-seeking behaviors. Concrete, time-bound plans for policy dissemination are necessary to ensure effective service implementation.